2017
DOI: 10.1177/0363546517732541
|View full text |Cite
|
Sign up to set email alerts
|

Return to Sport-Specific Performance After Primary Anterior Cruciate Ligament Reconstruction: A Systematic Review

Abstract: CRD42016046709 (International Prospective Register of Systematic Reviews, https://www.crd.york.ac.uk/prospero/ ).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
55
3
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(72 citation statements)
references
References 36 publications
8
55
3
2
Order By: Relevance
“…Compared to matched controls, a considerable lower share was still engaged in competitive football at 5 years post‐RTP, especially with regard to the same level of competition. A recently published systematic review revealed comparable amounts for total RTP rates: Depending on the source and type of sport, two‐third to all top‐level professional athletes successfully were found to return to their sport …”
Section: Discussionmentioning
confidence: 99%
“…Compared to matched controls, a considerable lower share was still engaged in competitive football at 5 years post‐RTP, especially with regard to the same level of competition. A recently published systematic review revealed comparable amounts for total RTP rates: Depending on the source and type of sport, two‐third to all top‐level professional athletes successfully were found to return to their sport …”
Section: Discussionmentioning
confidence: 99%
“…Several authors evaluated the factors associated with return to sports activity. 8 9 The importance of psychological response and fear of reinjury (kinesophobia) after ACL-R has been also recently underlined. 10 11 12 Paterno et al, in their retrospective study on 40 ACL-Rs, concluded that patients with greater fear of reinjury were four times more likely to gain lower level of activity, seven times more likely to have a single-hop limb asymmetry, and six times more likely to have a deficit of quadriceps strength greater than 90% compared with the contralateral limb.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, a highly challenging sport activity, which requires proper muscle control, may increase the risk of a new knee injury with repeat traumatic ACL rupture. [16][17][18][19] The time elapsed from surgery is often considered the most reliable criterion for granting the return to sporting gesture, and 6/7 months is considered a safe period by most surgeons. 5,8 Regarding professional players, coaches, agents, teammates, the player themselves, and family will often push the envelope on "cutting-edge surgical techniques" so that the player can return to sport as quickly as possible.…”
Section: Discussionmentioning
confidence: 99%